Freedmen (male and female) in Lima: 18th Century - Adanaque Velasquez, Raul (2009)
In the present investigation aims to explore the freedom in Lima during the eighteenth century. This will have an important collection of documents consisting of the wills of the freedmen and liberty of the century Lima indicated. Although these documents reveal the few possessions left, the freedmen were struggling to describe their heritage and those who decide to appoint as his heirs and how many assets they had. Of total freedom, the libertas were mostly those who had better opportunities to manage your will